2022
DOI: 10.1097/ccm.0000000000005711
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Difficult Laryngoscopy Using Ultrasound: A Systematic Review and Meta-Analysis

Abstract: OBJECTIVES: Evaluate associations between ultrasound measures and difficult laryngoscopy. DATA SOURCES: MEDLINE, Embase, Google Scholar, Web of Science, and the Cochrane Library were searched using MeSH terms and keywords. STUDY SELECTION: Studies published in English describing the use of airway ultrasound for identifying difficult laryngoscopy, with sufficient data to calculate sensitivity and specificity using 2 × 2 tables. DATA EXTRACTION: We assigned the described indices of airway dimension to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…[ 11 ] A recent systematic review showed that airway ultrasound metrics were associated with difficult laryngoscopy in three domains: anterior tissue thickness, anatomical position, and oral space. [ 12 ]…”
Section: Airway Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] A recent systematic review showed that airway ultrasound metrics were associated with difficult laryngoscopy in three domains: anterior tissue thickness, anatomical position, and oral space. [ 12 ]…”
Section: Airway Assessmentmentioning
confidence: 99%
“…Combining clinical and ultrasound assessments may form an accurate screening tool for difficult laryngoscopy in the future. [ 12 ]…”
Section: Airway Assessmentmentioning
confidence: 99%
“…However, the presence of a large amount of heterogeneity in the study methodology, measurement thresholds, and population groups has prevented the generalization of these tools at the bedside. Recent studies have suggested the role of assessment instruments combining clinical and ultrasound methods to predict difficult laryngoscopy more accurately 66 . Most of these studies have been done in adults, and few studies evaluate these metrics in children.…”
Section: Predicting Difficult Laryngoscopymentioning
confidence: 99%
“…The predictive value of individual tests is low due to the lack of standardized measurements, agreed‐upon cut‐off values, and the subjectivity of examination. However, a combination of multiple ultrasound metrics and clinical examination can predict difficult laryngoscopy with greater accuracy than a single measurement alone 66 . Very few studies have evaluated difficult laryngoscopy using ultrasound in pediatric patients 69 …”
Section: Predicting Difficult Laryngoscopymentioning
confidence: 99%
“…We appreciate the opportunity to respond to the communication by Foley (1) regarding our recently published article (2).…”
mentioning
confidence: 99%